AWARENESS ABOUT SPINAL ANAESTHESIA AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Spinal anaesthesia is administered in the lumbar spinal region and utilized for surgeries including the lower midsection, pelvis, and lower extremities. Spinal anaesthesia is acted in the lumbar region, explicitly the mid- to low-lumbar levels, to maintain a strategic distance from harm to the spinal cord and furthermore to forestall intrathecally administered drugs from having any action in the upper cervical and thoracic areas. The aim of the study is to assess the awareness about spinal anaesthesia among dental students. This was a questionnaire-based cross-sectional type of study comprising 100 dental college students in Chennai. A self-designed questionnaire contains 10 questions based on the knowledge and awareness about spinal anaesthesia among dental college students. Questionnaires were circulated through an online website survey planet. The questions explored awareness on spinal anesthesia, indications, contraindications, mechanism of administration, and side complications. After the responses were received from 100 participants, data was collected and analysed.18% are aware about spinal anaesthesia . 15% are aware of the mechanism of administration of spinal anaesthesia . 13% are aware of the indications of spinal anaesthesia . 11% are aware of the contraindications of spinal anaesthesia.9% are aware of the complications of spinal anaesthesia. The awareness about spinal anaesthesia was less among dental students.Increased awareness and educational programs should be initiated to spread knowledge about applications of spinal anaesthesia.